2014
DOI: 10.1080/09243046.2013.871173
|View full text |Cite
|
Sign up to set email alerts
|

XFEM for the evaluation of elastic properties of CNT-based 3-D full five-directional braided composites

Abstract: In the present work, a 3-D unit cell model is proposed to predict the elastic behavior of 3-D full five-directional braided composites. The model is analyzed by extended finite element method. An effective medium approximation scheme is used to evaluate the elastic properties of the composite. In the proposed unit cell model, the interface between the fiber and matrix is modeled by PU enrichment. The effects of fiber volume fraction and interior angle of braiding yarn on the elastic properties are analyzed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Eftekhari et al [24] developed an XFEM-multiscale approach to investigate the mechanical properties and fracture behavior of carbon nanotube (CNT)-reinforced concrete. Sahoo et al [25] proposed an XFEM-based scheme to evaluate the effective elastic properties of 3-D full five-directional braided composites. More recently, Negi et al [26] utilized the XFEM to conduct the study of crack growth in a thin rectangular plate containing an edge crack and a center crack and, subsequently, extended their approach to analyze the effect of additional defects in the form of voids and inclusions in the material [27].…”
Section: Introductionmentioning
confidence: 99%
“…Eftekhari et al [24] developed an XFEM-multiscale approach to investigate the mechanical properties and fracture behavior of carbon nanotube (CNT)-reinforced concrete. Sahoo et al [25] proposed an XFEM-based scheme to evaluate the effective elastic properties of 3-D full five-directional braided composites. More recently, Negi et al [26] utilized the XFEM to conduct the study of crack growth in a thin rectangular plate containing an edge crack and a center crack and, subsequently, extended their approach to analyze the effect of additional defects in the form of voids and inclusions in the material [27].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [15] presented an analytical method for designing a 3D five-directional braided composite joint. Sahoo et al [16] evaluated elastic properties of 3D full-directional properties. Yan et al [17] researched low-velocity impact behaviors of 3D five-directional carbon/epoxy braided composite panels with different braiding parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, research in this field has dealt with polymer/ CNT composites that offer remarkable strengthening impact for the subsequent materials [5]. Moreover, the literature has shown that the fracture toughness, shear, thermal, flexural, and tensile properties of polymerbased composite materials improve considerably with a 0.1-5 wt.% loading of CNTs [6,7]. Because of the interfacial interactions, mainly in the interphase of superficially functionalized polymer/CNT composite, recently few investigations have focused on the preparation and design of hybrid fiber/CNT composites by developing CNTs over fibers [8,9].…”
Section: Introductionmentioning
confidence: 99%